Trabalho e currículo oficial: contradições e tensões no modo de ser professor contemporâneo - reflexões sobre os livros-texto - Machado, Janete da Costa (2011)
This dissertation seeks a theoretical comprehension on the sort of education nowadays forged by the new public educational policies and its effects on learning and teaching praxis through normative and regulatory artifacts such as the Official Curricular System, concretely presented in Text Books. Therefore, inspired by the question: what are the effects of the official curricular system on learning and teaching praxis? , this research seeks to present a brief overview of education s commodification process and the consequent expropriation of teaching knowledge, by reflecting on the above mentioned Text Books. To attain such purposes, the research is based on qualitative survey and documentary and bibliographical analysis. Such basis was build on the theoretical assumptions of authors such as: Marx, Kosik, Vázquez, Paulo Freire, Tragtenberg, Mészáros, Leher, Gentili, Frigotto, Linhares, Torres Santomé, Apple, amongst others, that enabled the reflection of methodological and theoretical themes of the historical materialistic dialectics as the rational logic that expresses and aims at the appropriation of the reality by social being, in order to ontologically situate the specificity of the social being in human labor; foundation of all sort of praxis. By studying labor s division in capital s interest, the split between relational moments of mental and manual labor was analyzed, theory and practice, subjectivity and objectivity, design and execution a radiating center of contemporary contradictions and disposals. Therefore, the human labor as a producer and reproducer of global concrete class sociability, frames the social phenomenon of bureaucratization, the degeneration of the ontocreator praxis and of the human labor potentiality of freed labor from capital s rule. In this process one points out to the standardization of official knowledge and the growing expropriation of learning and teaching knowledge of concrete reality, bring it closer to education s conception and practice denominated by Paulo Freire as banking education . This scenario also unveils the ways of teaching although caught between concrete reality s contractions and the tensions arising from the powerful official political economic knowledge which transforms Education, from Social and Human Right, into Commodity. In summary this dissertation hopes to contribute with reflections that point to possible paths through with teachers can find breaches in and through praxis to overcome the market logic controlling public education s soul ascribed to working class children